Implementation of Gontornews.com Online Media Editorial Management - Salma Laila Qodriyah; Harmonis Harmonis (Sahafa Journal of Islamic Communication, 2024)
Gontornews.com is a boarding school website owned by Pondok Modern Gontor which has online media. The purpose of this study is to find out how management and editorial limitations are implemented at Gontornews.com, which includes matters such as planning, organizing, executing/directing, and supervising. This study uses a qualitative descriptive approach with case studies found on Gontornews.com, an online website. Primary and secondary data are collected through in-depth interviews with various relevant sources. This study was conducted from June to July 2022 in Jakarta. The results of the study show that Gontornews.com editorial management is used in reporting through various stages, starting from making plans, working with editorial members, sending news, and using references to books, newspapers, magazines, and other sources on the Internet. However, this study found that, even though the editorial management of Gontornews.com is very good, there are some obstacles in the news production process, such as limited reporters from within and outside the city, publication deadlines, and limited time for reporters who are out of sync. While there are some limitations, such as language limitations, external sources, and website systems, these obstacles can be overcome.